Isi Piringku Kaya akan Protein Hewani untuk Cegah Stunting - Heryani, Heni; Utami Asmarani, Sri; Setiawan, Henri; Endang Purwati, Ayu; Nurherliyany, Metty; Firmansyah, Andan; Lestari, Lusi (Yayasan Inspirasi El Burhani, 2025)
Introduction: Stunting remains a significant nutritional issue characterized by chronic malnutrition, negatively impacting children's growth, development, and productivity throughout their lives. Proper nutrition, particularly during the first 1,000 days of life, is essential to prevent stunting. The lack of protein intake, especially from animal sources, is a major contributing factor to stunting in Indonesia. Objective: The purpose of this public service was to increase the knowledge of mothers with toddlers and health cadres regarding the importance of animal protein intake as part of the